The Effect of World Oil Price Returns, Inflation Returns, and Interest Rate Returns on JCI Returns on the IDX for the Period 2020-2024 (Pusat Riset dan Inovasi Nasional, 2026)
The purpose of this study is to analyze the relationship between world oil price returns, inflation returns, and interest rate returns and the performance of the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange from 2020 to 2024. This study applies a quantitative approach using 60 monthly secondary data observations covering the entire research period. The sampling technique used is saturated sampling. Data analysis in this study was conducted using multiple linear regression to test the effect of each independent variable on the JCI return. The results show that world oil price returns have a positive and significant effect on the JCI return. Meanwhile, inflation returns and interest rate returns did not show a significant partial effect on JCI returns. However, simultaneously, these three variables were found to have a significant effect on JCI returns. The adjusted R-squared value of 0.345 indicates that the research model is able to explain 34.5 percent of the variation in JCI returns, while the rest is influenced by factors outside the research model.